RNS derivation of N-point disk amplitudes from the revisited S-matrix approach - Barreiro, Luiz Antonio [UNESP]; Medina, Ricardo (Elsevier B.V., 2014)
Recently, in [7] we proposed a revisited S-matrix approach to efficiently find the bosonic terms of the open superstring low energy effective lagrangian (OSLEEL). This approach allows to compute the alpha'(N) terms of the OSLEEL using open superstring n-point amplitudes in which n is considerably lower than (N + 2) (which is the order of the required amplitude to obtain those alpha'(N) terms by means of the conventional S-matrix approach). In this work we use our revisited S-matrix approach to examine the structure of the scattering amplitudes, arriving at a closed form for them. This is a RNS derivation of the formula first found by Mafra, Schlotterer and Stieberger [21], using the pure spinor formalism. We have succeeded doing this for the 5, 6 and 7-point amplitudes. In order to achieve these results we have done a careful analysis of the kinematical structure of the amplitudes, finding as a by-product a purely kinematical derivation of the BCJ relations (for N = 4, 5, 6 and 7). Also, following the spirit of the revisited S-matrix approach, we have found the alpha' expansions for these amplitudes up to alpha'(6) order in some cases, by only using the well known open superstring 4-point amplitude, cyclic symmetry and tree level unitarity: we have not needed to compute any numerical series or any integral involving polylogarithms, at any moment. (C) 2014 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/3.0/).